KONSEP PENDIDIKAN ISLAM MULTIKULTURAL DALAM PANDANGAN KH. MUHAMMAD THOLCHAH HASAN DAN ALI MAKSUM - Fadhlullah Makmun; Rosichin Mansur; Imam Safi’i (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Indonesia is the largest multicultural country in the world, considering the many cultures, religions, and races that exist in Indonesia. Therefore, education in Indonesia must use a multicultural-based approach, especially in Islamic education. This research will discuss the concept of multicultural Islamic education in the view of KH. Muhammad Tholchah Hasan and Ali Maksum, which a comparison was made of the two concepts, and the implications for Islamic religious education in Indonesia. The method in this research uses a qualitative approach with the type of literature study. In the results, it was found that the concept of multicultural Islamic education in the view of KH. Muhammad Tholchah Hasan is an education that must emphasize respect for diversity by promoting inclusive values of self-reliance. Meanwhile, Ali Maksum in his concept states that multicultural Islamic education is education about religious and cultural diversity in responding to socio-cultural changes in people's lives. There are differences and similarities in the two concepts. The difference is in the aspects of the background, foundation, and values. The similarities is in the aspects of the characteristics, objectives, curriculum development, and the learning morning. Both concepts have positive implications for Islamic religious education in Indonesia.